Utilization of dental services by preschool children: prevalence and associated factors - Isabela da Costa GONÇALVES; Valéria Silveira COELHO; Joana RAMOS-JORGE; Priscila Seixas MOURÃO; Kaio Henrique SOARES; Maria Letícia RAMOS-JORGE; Izabella Barbosa FERNANDES (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Dental associations worldwide recommend that the first dental visit should take place before 12 months of age; however, preschoolers' utilization of dental services remains low. The aim of this study was to assess the prevalence of, and factors associated with, dental services utilization among children aged 1 to 3 years. This was a cross-sectional study carried out in the city of Diamantina, MG, Brazil, and involved a sample of 308 child-mother pairs. Mothers completed a questionnaire addressing sociodemographic and economic aspects of the family and characteristics pertaining to their child's oral health. The clinical assessment of the children included dental caries, trauma, malocclusion, and mucosal changes. Analysis of the data comprised statistical description, application of the chi-square test, and Poisson's regression analysis. Among the children studied, 39.6% had attended at least one dental visit in their lifetime. Children whose families had a greater number of members relying on the family's income (PR = 1.40, 95%CI:1.04 -1.89, p = 0.028) and those with moderate/extensive dental caries (Codes 3-6 of the ICDAS; PR = 1.44, 95%CI: 1.08 -1.93, p = 0.014) exhibited a higher prevalence of dental services utilization. In conclusion, the prevalence of dental services utilization among children aged 1 to 3 years was low, and was associated with a greater number of family members relying on the family's income, and with the occurrence of moderate/extensive dental caries.